Monetization Models in Mobile Gaming: Analyzing User Preferences and Willingness to Pay Among Indonesian Players - Madepo, Mahardika Agung (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The mobile gaming industry has experienced rapid growth and is dominated by freemium/free-to-play models, making understanding of monetization preferences and willingness to pay (WTP) increasingly relevant. The study maps player preferences toward monetization models (free-with-ads, freemium with in-app purchase/IAP, and premium no-ads) and analyzes psychological factors influencing purchase intention (PI) and WTP. A quantitative cross-sectional survey was conducted with 210 active mobile game players (convenience and snowball sampling). WTP was measured in two stages: willingness to pay decision (WTP_bin) and maximum amount (WTP_Rp), with linear regression analysis for PI, logistic regression for WTP_bin, and linear regression on ln(WTP_Rp) for respondents willing to pay. Results show dominant preferences for free models: free-with-ads 54.3% and freemium IAP 30.5%, while premium no-ads 15.2%; payer proportion was 35.2%. Instruments demonstrated reliability (Cronbach's alpha 0.921–0.935). The PI model was significant (R²=0.640), where Perceived Value (PV) and Perceived Enjoyment (ENJ) had the strongest positive effects, followed by Quality, Fairness, and Social Norms, whereas Reference Price & Price Sensitivity (RPPS) and Perceived Aggressive Monetization (PAM) had significant negative effects. For WTP_bin, odds of becoming a payer increased with PV (OR=1.593) and decreased with RPPS (OR=0.468) and PAM (OR=0.651). Among payers (n=74), ln(WTP_Rp) increased with PV, ENJ, and Fairness, but was suppressed by PAM. Findings confirm the necessity of strengthening value, experience, and fairness while avoiding aggressive monetization to enhance conversion and payment amounts.